End-Stage Renal Disease Patients on Haemodialysis in Gezira State Central Sudan; Aetiology and Iron Status - Elgaili, Elgaili Mohd; Ahmed, Mohammed E. M.; Khalid, K.E. (Gezira Journal of Health Sciences, 2014)
Background: This cross sectional study was conducted to determine the possible causes of chronic renal failure (CRF) and to monitor the iron status in order to reduce the mortality and morbidity in dialysis patients. Resluts: Sixty eight CRF patients (36 men and 32 women) on regular haemodialysis were included in this study. Their mean age was 45.4 ± 17.8 years. Diabetes nephropathy (29%) was the commonest cause of CRF, followed by hypertension (21%), Glomerulonephritis (15%), Severe malaria (13%) and the least common one was polycystic kidney (3%). The mean serum iron was 57.7 ± 27.9 ng/ml, mean serum ferritin was 221.0 ± 170.1 ng/ml, and transferrin saturation (TSAT) was 22.8 ± 24.3%. Using TSAT, 15 (22.1%) patients had adequate (or normal) iron status (25.9 ± 4.4; 284.6 ± 111.0), 53 (77.9%) patients had iron deficiency (13.8 ± 2.6; 88.8 ± 37.7) and none had iron overload. Conclusion: Our study suggests that, diabetes and hypertension are the conditions requiring strategies for prevention and treatment, and iron status of most cases is poor.